Analysis of Total Proton Therapy Dose Distribution with Pencil Beam Collimator Model and Varied Beam Directions in Craniopharyngioma Tumor using MCNP6 Software - Hayati, Widia; Utari, Utari; Anwar, Fuad; Suharyana, Suharyana; Arianto, Fajar; Khakim, Azizul (Diponegoro University Semarang Indonesia, 2024)
Proton therapy modeling for treating craniopharyngioma tumors was conducted using a pencil beam collimator, and variations in beam directions were performed using MCNP6 software. The simulation was carried out on a head and neck phantom with the tumor cells modeled within a cubic irradiation area geometry with a 1.2 cm side length, divided into 27 small cubic voxels with a small voxel side length of 0.4 cm. The radiation source from the irradiation area's right, left, and top directions, with a diameter of 0.4 cm, was directed at each cubic voxel. Variation in radiation source directions indicated that irradiation from the right direction of the irradiation area is the most recommended approach, with a dose uniformity level of 83.47%. Healthy organs surrounding the irradiation area received lower doses than those obtained by tumor cells, and the majority remained below the Organ At Risk (OAR) threshold. Healthy organs received the highest dose, particularly in the brain region, at a relative 0.46% compared to the total dose received by tumor cells.